2003
DOI: 10.1080/15622970310029908
|View full text |Cite
|
Sign up to set email alerts
|

Dementia paralytica (neurosyphilis): A clinical case study

Abstract: This study reminds clinicians that syphilis presents in many guises. Wars, migration and sexual promiscuity prepare the ground for its return as an important cause of neurological and psychiatric syndromes. Our patient's diagnosis was not suspected at earlier admission. Stage III spirochaetosis was improved by high dose penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
1
0
4
Order By: Relevance
“…For instance, Fujimoto et al [6] reported a case who presented with immediate, recent and remote memory disturbances. This was consistent with previously reported cases [7,8,9,10,11]. Unfortunately, these studies lacked systematic neuropsychological examinations, and they did not include other dementia patient groups (e.g.…”
Section: Introductionsupporting
confidence: 91%
“…For instance, Fujimoto et al [6] reported a case who presented with immediate, recent and remote memory disturbances. This was consistent with previously reported cases [7,8,9,10,11]. Unfortunately, these studies lacked systematic neuropsychological examinations, and they did not include other dementia patient groups (e.g.…”
Section: Introductionsupporting
confidence: 91%
“…Reference was made to dementia more than 1700 years ago during the time of the Roman empire [240]. Throughout history, various types of dementia have been associated with (1) infections, e.g., neurosyphilis [241], kuru [242], Creutzfeldt-Jakob disease [243], and HIV-AIDS [244]; (2) genetic mutations, e.g., Huntington's disease [245], DS [246]; (3) vascular deterioration in the form of multi-infarct dementia [247]; (4) traumatic head injury, e.g., post-traumatic dementia [248] and dementia pugilistica [249]; and (5) environmental or lifestyle factors, e.g., dialysis dementia [35], Balint's syndrome (an occupational dementia) [36], ALS/PD [250], and Wernicke-Korsakoff Syndrome or alcohol-related dementia [251]. In 1979, AD accounted for closer to 50% of all dementia cases [252].…”
Section: Historical Perspective Of Ad and Other Dementiasmentioning
confidence: 99%
“…B. Primäraffekte oder Syphilide werden von kognitiv beeinträchtigten Patienten nicht wahrgenommen oder schizophrene Patienten suchen trotz syphilitischer Effloreszenzen keinen Arzt auf) [40]. Schließlich sollte bei allen Patien− ten mit neu aufgetretenen psychotischen oder demenziellen Zustandsbildern der Liquor unter− sucht werden, um eine Neurosyphilis differenzi− aldiagnostisch ausschließen respektive frühzei− tig behandeln zu können [34]. Auch wenn eine Restitutio ad integrum bei bereits eingetretenem Hirnparenchymverlust nicht mehr möglich ist, so ist zumindest die Defektheilung bzw.…”
Section: Symptomatische Therapie Mit Psychopharmakaunclassified
“…Nach Rolfs u. Mitarb. [39] liegt eine Therapiebedürftigkeit vor bei positivem 19S−IgM−FTA−ABS und/oder bei VDRL mit einer Titerstufe von mindestens 1 : 8 oder einer Titerer− Neben einer eingehenden psychiatrischen und neurologischen Befunderhebung sind serologische und Liquoruntersuchungen zur Diagnostik der Neurosyphilis unerlässlich.mehr Jahren, eine Liquorpunktion zum Aus− schluss einer Neurosyphilis indiziert[34]. Prinzi− piell gilt, dass bei allen Syphilis−HIV−koinfizier− ten Patienten eine Liquoruntersuchung durchge− führt werden soll, da bis zu 40 % dieser Patienten bereits im Sekundärstadium der Syphilis einen pathologischen Liquorbefund aufweisen[16].Die progressive Paralyse führt unbehandelt zu vegetativem Verfall mit letalem Ende.…”
unclassified